2019
DOI: 10.7554/elife.42129
|View full text |Cite
|
Sign up to set email alerts
|

CtIP forms a tetrameric dumbbell-shaped particle which bridges complex DNA end structures for double-strand break repair

Abstract: CtIP is involved in the resection of broken DNA during the S and G2 phases of the cell cycle for repair by recombination. Acting with the MRN complex, it plays a particularly important role in handling complex DNA end structures by localised nucleolytic processing of DNA termini in preparation for longer range resection. Here we show that human CtIP is a tetrameric protein adopting a dumbbell architecture in which DNA binding domains are connected by long coiled-coils. The protein complex binds two short DNA d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 41 publications
10
40
0
Order By: Relevance
“…For the linearized DNA, multiple complexes are observed with protein clusters associated along the contour of the DNA molecule. Furthermore, linear complexes were also observed with protein clusters localized at the ends, suggesting specific DNA end interaction, in agreement with previous reports on the CtIP function (27,37). We also performed AFM experiments for CtIP L27E , which preferentially promotes the formation of intermolecular complexes, which requires binding to free DNA ends.…”
Section: Nanofluidics Allows Detection and Differentiation Between LIsupporting
confidence: 90%
See 3 more Smart Citations
“…For the linearized DNA, multiple complexes are observed with protein clusters associated along the contour of the DNA molecule. Furthermore, linear complexes were also observed with protein clusters localized at the ends, suggesting specific DNA end interaction, in agreement with previous reports on the CtIP function (27,37). We also performed AFM experiments for CtIP L27E , which preferentially promotes the formation of intermolecular complexes, which requires binding to free DNA ends.…”
Section: Nanofluidics Allows Detection and Differentiation Between LIsupporting
confidence: 90%
“…The significant decrease in circularization efficiency for the structural mutants CtIP L27E and CtIP Δ160 suggests that the previously reported tetrameric structure (27) of wtCtIP imposes a key role in bridging DNA. You et al (37) reported that modifying a minimal damage recruitment (DR) motif (amino acids 509 to 557) in CtIP exerted a down-regulating effect on the damage recruitment capacity, possibly due to the reduced DNA-binding ability of the protein.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The activated MRN complex then preferentially cleaves the 5′terminated DNA strand past protein blocks. Therefore, this step is particularly important to process DNA ends with noncanonical structures, including bound proteins like Ku and topoisomerase-DNA cleavage complexes, as well as secondary DNA structures (14)(15)(16)(17)(18). CtIP is phosphorylated by multiple kinases including CDK, ATM, and ATR.…”
mentioning
confidence: 99%